2006
DOI: 10.1089/jpm.2006.9.1376
|View full text |Cite
|
Sign up to set email alerts
|

Existential Loneliness in a Palliative Home Care Setting

Abstract: The data revealed experiences of existential loneliness with the impending death as a primary source. Experiences of being alone in "a world of one's own" were common. The changes in everyday life and the increasingly restricted social interaction because of the illness meant that the patient partly lost the protection against isolation that the spirit of community normally provides. Other situations that had a triggered the existential isolation were, for example, when a patient in need of support was left al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
171
0
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(190 citation statements)
references
References 15 publications
7
171
0
12
Order By: Relevance
“…Specific themes found in other research are echoed here, including lack of control over bodies (Chapple & Ziebland, 2002;Kelly, 2008), bodily changes as warnings of impending death Sand et al, 2009), uncertainty and unknowing during the palliative care stage (Nissim, et al, 2012), feelings of social separation ( Koffman et al, 2012) and existential loneliness (Strang & Sand, 2006). Similarly, other research has found that cancer survivors and those living with advanced cancer show an increased awareness of time, difficulty in reflecting on future time and sense of a receding future (Cecil et al, 2010;Rasmussen & Elverdam, 2007).…”
Section: Discussionsupporting
confidence: 59%
“…Specific themes found in other research are echoed here, including lack of control over bodies (Chapple & Ziebland, 2002;Kelly, 2008), bodily changes as warnings of impending death Sand et al, 2009), uncertainty and unknowing during the palliative care stage (Nissim, et al, 2012), feelings of social separation ( Koffman et al, 2012) and existential loneliness (Strang & Sand, 2006). Similarly, other research has found that cancer survivors and those living with advanced cancer show an increased awareness of time, difficulty in reflecting on future time and sense of a receding future (Cecil et al, 2010;Rasmussen & Elverdam, 2007).…”
Section: Discussionsupporting
confidence: 59%
“…In a systematic review by Hallberg (2004) into older people’s views on death and dying, older people showed a need to talk about existential issues, of time past and time to come, as well as of dying and death. If existential thoughts and reflections at this point are not recognized or affirmed, anxiety or existential loneliness (feeling alone in the world despite having people around) can arise (Sand & Strang, 2006). This suggests a need for further exploration to deepen our understanding of existential loneliness in the caring context.…”
Section: Introductionmentioning
confidence: 99%
“…Death causes an existential crisis for many people, especially those who are facing a life-threatening disease. According to Sand and Strang [2] , the inevitability of death triggers an existential crisis that involves patients' and families' emotions and perceptions. This leads them to experience existential isolation.…”
Section: Introductionmentioning
confidence: 99%